Aplikasi System Presensi Mahasiswa Dengan Menggunakan Barcode Pada Laboratorium Fakultas Ilmu Komputer UMI - Fadli Tamrin (Celebes Computer Science Journal, 2020)
Absence of Student of Faculty Computer Science specially at Laboratory still using of manual absence on that account to facilitate the dosen and assistant lab call the roll the student hence writer make the system of absence of using barcode. Writer make the absence program by using Ianguage of pemrograman borland delphi, database Mysql and appliance of scan barkode. With the existence of the absence appliance presumably can assist the job of dosen and assistant lab in calling the roll incoming student, this absence system beryl can summarize the student data in bracket certain time. madely of absence system use this barcode, writer expect this system can assist the process school activity specially student absenc